2014
DOI: 10.1515/bmc-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of meiotic entry and gonadal sex differentiation in the human: normal and disrupted signaling

Abstract: Meiosis is a unique type of cell division that is performed only by germ cells to form haploid gametes. The switch from mitosis to meiosis exhibits a distinct sex-specific difference in timing, with female germ cells entering meiosis during fetal development and male germ cells at puberty when spermatogenesis is initiated. During early fetal development, bipotential primordial germ cells migrate to the forming gonad where they remain sexually indifferent until the sex-specific differentiation of germ cells is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“…In the ovary germ cells enter meiosis in fetal life, whereas in fetal testes the meiotic entry is actively inhibited ensure male germ cell development (reviewed in [64]. Initiation of meiosis in humans is at least in part dependent on the action of retinoic acid (RA) [27,[65][66], which induces expression of the pre-meiosis marker STRA8 [65][66].…”
Section: Sex-dimorphic Regulation Of Meiosis In Fetal Germ Cellsmentioning
confidence: 99%
“…In the ovary germ cells enter meiosis in fetal life, whereas in fetal testes the meiotic entry is actively inhibited ensure male germ cell development (reviewed in [64]. Initiation of meiosis in humans is at least in part dependent on the action of retinoic acid (RA) [27,[65][66], which induces expression of the pre-meiosis marker STRA8 [65][66].…”
Section: Sex-dimorphic Regulation Of Meiosis In Fetal Germ Cellsmentioning
confidence: 99%
“…In this setting, PGCs, now termed gonocytes, begin to multiply rapidly. At 17–18 weeks of gestation, gonocytes begin to mature into pre-/fetal spermatogonia, a process involving down-regulation of pluripotency factors, gradual migration to the basal lamina of the sex cords, and a relative quiescence until after birth [10,11]. Following testicular descent at or around birth, a surge in testosterone production and other testicular hormones occurs [12].…”
Section: Introductionmentioning
confidence: 99%
“…TGCC is believed to arise from germ cell neoplasia in situ (GCNIS) cells (Skakkebaek et al, 1987;Albers et al, 2011;Rajpert-De Meyts et al, 2015;Moch et al, 2016), which are assumed to originate from foetal gonocytes that failed to develop into spermatogonia due to niche disturbances affecting the Sertoli cells (Rajpert-De Meyts et al, 2015). Little is known about the role of FSH activity for early germ cell differentiation, but there is a clear sexual difference in the foetal FSH levels with considerably lower levels in the male foetus compared to female (Clements et al, 1976) and it has previously been suggested that GCNIS cells may be 'sexually confused' by the inadequately virilized somatic niche during testis development (Jørgensen & Rajpert-De Meyts, 2014). FSH transiently increases during minipuberty, and there is some evidence that boys with cryptorchidism, a risk group for TGCC, have increased FSH levels already during this period (Suomi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%